Identification and Genotyping of Transposable Element Insertions From Genome Sequencing Data. (14th July 2020) - Chu, Chong; Zhao, Boxun; Park, Peter J.; Lee, Eunjung Alice
Abstract: Transposable element (TE) mobilization is a significant source of genomic variation and has been associated with various human diseases. The exponential growth of population‐scale whole‐genome sequencing and rapid innovations in long‐read sequencing technologies provide unprecedented opportunities to study TE insertions and their functional impact in human health and disease. Identifying TE insertions, however, is challenging due to the repetitive nature of the TE sequences. Here, we review computational approaches to detecting and genotyping TE insertions using short‐ and long‐read sequencing and discuss the strengths and weaknesses of different approaches. © 2020 Wiley Periodicals LLC.